Dynamic stability of iron oxide-ethylene glycol nanofluids - Alagappan Subramaniyan; Nitun Periyasamy (Iranian Journal of Physics Research, 2022)
Nanopowders/Nanostructures have attracted the attention of engineers and scientists for their tunable properties and extended applications. One of the extended application of nanopowders is nanofluids. Nanofluids are assumed as the most preferred next generation coolants and their stability is essential for their successful implementation. Iron oxide nanoparticles were prepared by the sol-gel method using Ferrous sulphate as precursors. The prepared nanoparticles were characterized by XRD and photo luminescence. Iron oxide nanofluids (0.1 & 0.3 vol%) with ethylene glycol as base fluid were prepared by a two-step method. The nanofluids were tested for dynamic stability (at 1, 3, 6, 12 and 24-hour intervals). The variation in zeta potential with time is analyzed to predict their stability transformations. We observe that 0.3 vol% nanofluid exhibits better dynamic stability characteristics than the less stable 0.1 vol% nanofluid